ANALYZING EMPLOYEES’ PERCEPTION OF TRADITIONAL AND MODERN RECRUITMENT - Kaharuddin, Indira Wardhani; Pangemanan, Sifrid S.; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2018)
Abstract: Recruitment process has been evolved along with emerging technological innovations. The process of seeking and applying job now can be conduct in two ways, through traditional and through the modern system. In traditional recruitment, applicants are using physical sources and worth of mouth as a source to find vacancies and applied their resume directly to the company. While in modern or what also called e-recruitment applicants could find the information of job descriptions in the internet and applied their resume through the online system as well, such as corporate website and email. This research aims to analyze on the employees’ perception of traditional and modern recruitment. This research is using qualitative research to gain a deeper understanding about the topic and the type of this research is exploratory research. Population in this research are all elements that can be respondent which are the employees which believes had the experiences of seeking and applying for job. The result of this research shows that traditional recruitment is more effective from the employees’ perspective because it bring them higher opportunities get a position in the applied company. Researcher recommend for the organization to provide exact and certain process in their online system. Keyword : recruitment techniques, traditional recruitment, modern recruitment, employees’ perception